MOBILE GEOPHYSICAL TECHNOLOGIES USING FOR EXPRESS ASSESSMENT OF THE OIL, GAS AND ORE PROSPECTS AT THE REGIONAL AND LOCAL STAGES OF INVESTIGATIONS - Levashov, S.; Yakimchuk, M.; Korchagin, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The particularities and possibility of mobile geophysical technology are described. Technology include a special method of the remote sensing data processing and interpreting, aerial mapping method of the forming short-pulsed electromagnetic field (FSPEF), method of vertical electric-resonance sounding (VERS), computerized measuring instruments, software of the measurement data registrations, processing and interpretation, methods of the field observations conducting. Inclusion of such technologies in traditional complex of exploration geological-geophysical methods will promote both minimization of the financial expenses on the oil-and-gas exploration problems solving, and essential reduction of time for their practical realization.